2019
DOI: 10.1002/er.4841
|View full text |Cite
|
Sign up to set email alerts
|

A spiral shaped regenerative microfluidic fuel cell with Ni‐C based porous electrodes

Abstract: Summary Microchannel geometry, electrode surface area, and better fuel utilization are important aspects of the performance of a microfluidic fuel cell (MFC). In this communication, a membraneless spiral‐shaped MFC fabricated with Ni as anode and C as a cathode supported over a porous filter paper substrate is presented. Vanadium oxychloride and dilute sulfuric acid solutions are used as fuel and electrolyte, respectively, in this fuel cell system. The device generates a maximum open‐circuit voltage of ~1.2 V,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The maximum power density generated was comparable with that of a previous device [134]. Arun et al [136] developed a vanadium-based spiral-shaped SSMMFC using a carbon cathode and Ni anode with a fuel-electrolyte mixture of VOCl 3 and diluted H 2 SO 4 , as shown in Figure 7b. The spiral-shaped microchannel was built on a 1.5-mm-thick PMMA sheet with a laser engraving machine.…”
Section: Ssmmfcssupporting
confidence: 64%
“…The maximum power density generated was comparable with that of a previous device [134]. Arun et al [136] developed a vanadium-based spiral-shaped SSMMFC using a carbon cathode and Ni anode with a fuel-electrolyte mixture of VOCl 3 and diluted H 2 SO 4 , as shown in Figure 7b. The spiral-shaped microchannel was built on a 1.5-mm-thick PMMA sheet with a laser engraving machine.…”
Section: Ssmmfcssupporting
confidence: 64%
“…A resourceful alternative approach to reduce the noble metal content is the synthesis of core–shell catalysts, in which a less costly non-noble metal core is coated with a metal shell with higher electrocatalytic activity. In this regard, other catalyst materials for μFCs have been reported including gold, copper, cobalt, silver, iridium, iron, and nickel. ,,,,, While this approach may result in more rigorous catalyst synthesis processes, it may also be a way of reducing the electrocatalyst cost without compromising the electrocatalytic activity . For the ORR at the cathode, Pt has also been typically applied and shown higher activity than Pd.…”
Section: Devices and Applicationsmentioning
confidence: 99%
“…Experimental data revealed that the cell stacks were simpler, and performance was guaranteed. Ravi Kumar Arun introduced a spiral-shaped MFEFC with an anode made of Ni and a cathode made of C. 90 This cell was very effective in improving fuel utilization and eliminating crossover of fuel and electrolytes. Experimental data revealed that the spiral-shaped design enhanced fuel utilization and faster transport of ions.…”
Section: Different Design Practices Of Mfefcsmentioning
confidence: 99%